Ocular myasthenia gravis: controversies and updates. - Wong, S; Huda, S; Vincent, A; Plant, G (2014)
The majority of patients with myasthenia gravis (MG) initially present with ocular symptoms. An unresolved question is whether there are clinical features at onset to guide clinicians to predict an individual patient's conversion risk from ocular MG (OMG) to generalized disease, or "secondary generalized MG" (SGMG), that is, a prognostic model. In light of the emerging theory that early corticosteroids may have a risk-modifying effect, the factors associated with secondary SGMG previously reported should be revisited. Studies showing potential risk-modifying effects of corticosteroids are useful, though flawed, owing to the heterogeneous retrospective studies and methods of reporting. Updates on other potential immunosuppressive agents are also discussed. Thymectomy in OMG has been recently reported in a few studies to be useful. MG associated with antibodies to muscle-specific kinase, usually associated with severe generalized MG, can cause a pure OMG syndrome. Recent serological developments in seronegative patients have also revealed antibodies to clustered anti-acetylcholine receptor and lipoprotein receptor-related protein-4.